Clinico-Radiological Profile of Mesenteric Lymphadenitis in Children in a Tertiary care Institute of Central India - Valecha, Jyoti; Chanchlani, Roshan; Tripathi, Purva (International Journal of Medical Research and Review, 2015)
Background: Mesenteric adenitis is self-limiting inflammatory process mimicking appendicitis and affects the mesenteric lymph nodes in the right lower quadrant. Ultrasonography with graded compression is the main modality to diagnose this entity. Aim: of this study was to evaluateand analyse the incidence of enlarged mesenteric nodes with ultrasound in pediatric patients referred for abdominal pain. Material and Method: A total 100 patients attending paediatric and paediatric surgery clinic in Chirayu Medical College and hospital Bhopal, from May 2011 to May 2014 presenting with abdominal pain of various causes were included in this study. The presence of enlarged nodes, their location, size and other ultrasonographic findings were recorded. Final diagnosis was established after patient management and follow up. Result: On the basis of this study, it was observed that the incidence of enlarged lymph nodes increases with age with the peak incidence is at around 7 years range (5-8) years and decrease thereafter. A review of the dimensions of the lymph nodes detected shows that the transverse diameter of the lymph nodes was by and large always greater than the antero- posterior diameter .The maximum transverse diameter values was seen between 10- 14 mm whereas antero- posterior diameter values was seen between 4-8 mm. Our study also showed that the 80% of the lymph nodes were seen in the right lower quadrant followed by 12% in the left lower quadrant and 8% in the peri-aortic region. Conclusion: The possible variation in the clinical presentation of abdominal pain due to mesenteric lymphadenitis is a challenging task for physicians to diagnose. Mesenteric lymphadenitis is found to be self limiting entity, usually viral in origin. Hence surgical intervention can be avoided if diagnosis is accurately made.